Large‐Scale, Ultrasensitive, Highly Reproducible and Reusable Smart SERS Platform Based on PNIPAm‐Grafted Gold Grating1. Issue 2 (16th January 2017) - Guselnikova, Olga; Postnikov, Pavel; Kalachyova, Yevgeniya; Kolska, Zdenka; Libansky, Milan; Zima, Jiri; Svorcik, Vaclav; Lyutakov, Oleksiy
Abstract: A smart plasmonic sensor based on periodic gold gratings grafted with poly( N ‐isopropyl acrylamide) (PNIPAm) has been designed and realized. A periodic gold structure was created on the polymer backing with an excimer laser (1×2 cm 2 modified area) and was subsequently covered by thin gold film. In the next step, a 7 nm thick PNIPAm layer was grafted to the gold surface through a two‐step procedure: covalent attachment of 4‐carboxybenzil groups followed by carboxyl groups activation and their coupling with amino‐terminated PNIPAm. Surface properties of the prepared structure and their switchable behavior were investigated using refractometry, wettability measurements, AFM in water, cyclic voltammetry, and pH‐ and temperature‐dependent Z‐potential measurements. The structure enables effective entrapment and SERS detection of azo dyes, significant reduction of minimal detectable concentration of target molecules, and a detection limit down to femtomolar concentrations. Excitation of plasmons on the well‐ordered surface structure also gives excellent reproducibility for SERS along the particular sample surface and as well as on different samples. Additionally, the reversible switching of wettability under repeated temperature changes on the gold plasmonic platform allows multiple uses of the developed system. Abstract : Yes, SERS ! A periodic gold structure grafted with PNIPAm was used as smart, temperature‐tunable SERS sensor. The structure enables effective entrapment and SERS detection of azo dyes, with femtomolar detection limit. Excitation of plasmons on the well‐ordered surface structure gives excellent reproducibility of SERS, when the reversible switching of wettability under temperature changes allows multiple uses of the developed system.